Site Planning and Design Handbook - Russ, Thomas H. (McGraw-Hill's AccessEngineering., 2002)
Includes Federal and other regulations and ADA site requirements. Covers sustainable practices such as storm water rehabilitation and quality assurance. Includes guidance on project management issues including permitting and quality assurance.